Exploring Teachers’ Perspectives on Slow Learners in the Science Classroom - Acharya, Bisna; Sigdel, Surya; Poudel, Omkar (International Journal of Silkroad Institute of Research and Training, 2023)
Background: Educators encounter a significant challenge when it comes to instructing students with slower learning abilities in the field of science classroom. Students with limited cognitive abilities are typically identified as slow learners. The objective of this study was to examine the attitudes of teachers towards students with slower learning abilities in science classrooms and analyze their perceptions of these students. Methods: The study has been conducted by selecting a sample of 51 science teachers who teach at basic and secondary school levels. A representative sample of 51 teachers, who teach at basic and secondary level, were selected from 6 public schools in Chandragiri Municipality, Kathmandu district and 10 public schools in Ratnanagar Municipality, Chitwan district. The required data were gathered using a survey that employed three-point Likert-type questionnaires. The data were analyzed using frequency and percentage analysis. Results: The findings indicate that the science teachers exhibited a positive attitude towards students who have a slower learning pace. Conclusions: It is recommended to prioritize the enhancement of their science learning experience.